Anatomy and physiology in health and illness : Ross & Wilson - Waugh, Anne, ....-; Grant, Allison, ....- ([s.l.] : Elsevier, 2018)
Latest edition of the world's most popular textbook on basic human anatomy and physiology with over 1.5 million copies sold worldwide Clear, no nonsense writing style helps make learning easy Accompanying website contains animations, audio-glossary, case studies and other self-assessment material, the unique Body Spectrum online colouring and self-test software, and helpful weblinks Includes basic pathology and pathophysiology of important diseases and disorders Contains helpful learning features such as Learning Outcomes boxes, colour coding and design icons together with a stunning illustration and photography collection Contains clear explanations of common prefixes, suffixes and roots, with helpful examples from the text, plus a glossary and an appendix of normal biological values. Particularly valuable for students who are completely new to the subject, or returning to study after a period of absence, and for anyone whose first language is not English All new illustration programme brings the book right up-to-date for today's student Helpful 'Spot Check' questions at the end of each topic to monitor progress Fully updated throughout with the latest information on common and/or life threatening diseases and disorders Review and Revise end-of-chapter exercises assist with reader understanding and recall Over 120 animations - many of them newly created - help clarify underlying scientific and physiological principles and make learning fun
The new edition of the hugely successful Ross and Wilson Anatomy & Physiology in Health and Illness continues to bring its readers the core essentials of human biology presented in a clear and straightforward manner. Fully updated throughout, the book now comes with enhanced learning features including helpful revision questions and an all new art programme to help make learning even easier. The 13th edition retains its popular website, which contains a wide range of 'critical thinking' exercises as well as new animations, an audio-glossary, the unique Body Spectrum online colouring and self-test program, and helpful weblinks. Ross and Wilson Anatomy & Physiology in Health and Illness will be of particular help to readers new to the subject area, those returning to study after a period of absence, and for anyone whose first language isn't English.